pH and time effectiveness on azithromycin drug: A spectrophotometric approach - Saeed, Adel Ahmed; Al-Salimi, Mokhtar Salim; Muthanna, Amani Khalid; Saleh, Maysa Thabet; Ahmed, Ahmed Hassan; Qasam, Fadhel Mahmoud; Alwan, Hadeel Adnan; Alturky, Ibrahim Mukhtar; Hamood, Musab Muhammed (European Journal of Chemistry, 2024)
The present study describes a straightforward method to assess the quality control and diagnostic characteristics of three different brands of film-coated azithromycin tablets. The method is based on the reduction of potassium permanganate in a slightly alkaline solution using azithromycin. The effects of acidity and time were investigated to evaluate the reliability of the method. A spectroscopic technique was used to determine the concentration of azithromycin in a sample by measuring the decrease in potassium permanganate absorbance at a specific wavelength of 547 nm. Azithromycin causes decolorization of potassium permanganate with reduction. The method allowed the determination of azithromycin concentrations ranging from 3-15 μg/mL in the final solution. The usual components present in the azithromycin tablets were observed not to interfere with the method. The results obtained for the determination of azithromycin in tablets were in good agreement with the allowed limit.